Trends in hospitalization and mortality in COVID-19 admitted patients after a single dose of vaccine - Tirumala Bukkapatnam Ramakrishna; Uma Pokala; Sasikala Kanapalli; Naveen Pokala; Uday Kumar P (Asian Journal of Medical Sciences, 2023)
Background: Several types of vaccines are available across the world. Efficacy in preventing disease or reducing severity in terms of hospitalization, morbidity, and mortality needs to be studied in vaccinated patients, as most of them fail to prevent COVID-19 infections. Aims and Objectives: We aimed to correlate the disease severity and impact of a single dose of vaccine in COVID-19 breakthrough infections. Materials and Methods: The present study included 348 COVID-19 patients admitted to a tertiary hospital in Telangana, India, from March to August 2021 (and divided into an elderly group as Group 1 and a middle-aged group as Group 2 according to the vaccination protocol). Data were taken from the medical records of patients retrospectively regarding demographic and clinical details, as well as vaccination status during their hospital stay. Results: Diabetes mellitus and hypertension were found to be prevalent together as comorbidities (40%) in patients with prolonged hospitalization and 36% in those with severe disease (assisted ventilation). In vaccinated groups, irrespective of age, prolonged hospitalization was drastically halved (PR=0.418 for Group 1 and PR=0.416 for Group 2). Overall mortality in Group 1 is 2 times more frequent than in the Group 2 (odds ratio=2.12). Overall, prolonged hospital stays need for ventilatory support and deaths were also 2 times more common in men than in women. Conclusion: Older age, male gender, and more than one comorbidity are the most important factors determining poor clinical outcomes in persons with breakthrough severe acute respiratory syndrome coronavirus 2 infection, whereas vaccination is associated with a strong protective effect.